Spatial Regulation, Politics of Access and Informal economic Policy: The case of Durban Metro - Seroala Tsoeu-Ntokoane (African Journal of Governance and Development, 2024)
Analyses of the informal economy and the transition from apartheid have tended to draw attention to the political contestation over space. The city was ‘invaded’ and ‘conquered’ by traders who were formerly excluded (Nesvag, 2000, 2001; Tsoeu, 2003). At the same time, attention is drawn to the current attempts by city managers to control and regulate this contested space in an environment of flux. There are points of comparison; street trading has evolved a lot from what it was in the immediate1990’s post-apartheid period. This paper attempts to show that even in the post-transformation period, the regulatory regime is constantly changing as traders andurban managers negotiate, contest and confront images and practices held up by each as the most desirable outcomes of different views and uses of city space. To achieve this, the paper first looks briefly at the context of Durban Unicity, then goes on to consider at length, the regulatory regime(s) that govern the conduct and experience of street trading in Durban.